EAI International Conference on Technology, Innovation, Entrepreneurship and Education TIE'2017 - Reyes-Munoz, Angelica; Zheng, Ping; Crawford, David; Callaghan, Victor (Lecture Notes in Electrical Engineering, 2019)
This book presents the proceedings of the 1st EAI International Conference on Technology, Innovation, Entrepreneurship and Education (TIE 2017), which took place at Canterbury Christ Church University on September 11-12, 2017. The central theme of the conference is creativity and innovation, especially in relation to technology, business, education, social and political needs that make modern society flourish. The proceedings feature papers from a cross-disciplinary audience that explore the process of creativity and innovation. The goal is that the various disciplines can learn from each other and see how they might benefit from the cross-fertilization of practices.